Microwave Photonic Filter Based All-Optical Virtual Private Network Supporting Dynamic Bandwidth Allocation in OFDMA-PON System - Chang-Hun Kim; Sun-Young Jung; Sang-Kook Han (IEEE Photonics Journal)
We propose an all-optical virtual private network (VPN) supporting dynamic bandwidth allocation (DBA) in an orthogonal frequency division multiple access-based passive optical network. A microwave photonic bandpass filter (MP-BPF) is used to transmit the VPN signal without electrical conversion. The DBA is implemented by adjusting a free spectral range of the MP-BPF with corresponding subcarrier allocation. A RF clipping-tone (CT) is used to stabilize the optical channel suffered from phase induced-intensity noise and Rayleigh back-scattering noise. The DBA is experimentally verified at different two DBA scenarios in 20-km single-fiber loopback link in terms of channel error vector magnitude, spectral efficiency after adaptive modulation. Due to the CT-based channel stabilization, achievable spectral efficiency could be improved, and the feasibility of the proposed system is successfully demonstrated.